Sistem Jemuran Pakaian Cerdas Berbasis Internet of Things (IoT) - Hermawaty; Rifan Budi Resmana (Jurnal ICT: Information Communication & Technology, 2025)
Abstract- The development of information and communication technology (ICT) makes humans more creative in creating a system that will be used to facilitate their daily activities. One of the uses of this technology is an automatic clothesline system that helps protect clothes being dried from situations and conditions when it rains by utilizing microcontroller devices and sensor modules so that it becomes urgent for people who are carrying out activities outside the home so that they don't need to worry about their clothesline if it rains suddenly. The purpose of this study is to develop a prototype of an automatic clothesline using an Arduino microcontroller, raindrop sensor, servo motor and Internet of Things (IoT) technology. The microcontroller will process the data information received from the sensor and then send it to the thingspeak cloud computing and at the same time also give instructions to the motor driver to rotate and move left or right so that the clothesline protective roof can be active and protect the clothesline from rain. Information about real-time data and conditions on the system can be accessed by users using mobile devices on the thingsview application. The method that will be used is the experimental research method with a waterfall pattern, which can properly test the hypothesis concerning casual relationships through the design science research method (DSRM) stages. By making an automatic clothes drying tool, it will solve the problem for people who do not have time to take care of clothes drying when they are not at home and do not need to worry about clothes that are being dried because they are afraid of getting rained on.